2022
DOI: 10.1044/2021_jslhr-21-00383
|View full text |Cite
|
Sign up to set email alerts
|

Individuals With Congenital Amusia Show Degraded Speech Perception but Preserved Statistical Learning for Tone Languages

Abstract: Purpose: Individuals with congenital amusia exhibit degraded speech perception. This study examined whether adult Chinese Mandarin listeners with amusia were still able to extract the statistical regularities of Mandarin speech sounds, despite their degraded speech perception. Method: Using the gating paradigm with monosyllabic syllable–tone words, we tested 19 Mandarin-speaking amusics and 19 musically intact controls. Listeners heard increasingly long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…More importantly, the authors found that in early gates containing truncated speech (e.g., consonant onset and up to 120 ms of the vowel) amusics-like control listeners-identified frequent syllables more accurately than less frequent syllables and more probable tones more accurately than less probable tones (given the syllable). In other words, Zhu et al (2022) demonstrated that amusics tracked statistical regularities of segments and tones embedded in their native speech in a manner similar to control listeners (Wiener & Ito, 2016;Wiener & Lee, 2020). What remains unclear, and is the focus of the present study, is whether amusics can learn statistical regularities involving phonological tone in a non-native language within a brief training period involving distributional learning.…”
Section: Statistical Learning Of Pitch In Congenital Amusicsmentioning
confidence: 60%
See 3 more Smart Citations
“…More importantly, the authors found that in early gates containing truncated speech (e.g., consonant onset and up to 120 ms of the vowel) amusics-like control listeners-identified frequent syllables more accurately than less frequent syllables and more probable tones more accurately than less probable tones (given the syllable). In other words, Zhu et al (2022) demonstrated that amusics tracked statistical regularities of segments and tones embedded in their native speech in a manner similar to control listeners (Wiener & Ito, 2016;Wiener & Lee, 2020). What remains unclear, and is the focus of the present study, is whether amusics can learn statistical regularities involving phonological tone in a non-native language within a brief training period involving distributional learning.…”
Section: Statistical Learning Of Pitch In Congenital Amusicsmentioning
confidence: 60%
“…Pertaining to the learning outcome, amusics could show no improvement after training in either distribution condition given that they were afflicted with the pitch-processing disorder of amusia (Vuvan et al, 2015). Meanwhile, as mentioned earlier, because several studies did uncover that amusics were able to learn speech sounds in a statistical manner (Omigie & Stewart, 2011;Peretz et al, 2012;Zhu et al 2022), it was also expected that for non-native lexical tones, the perceptual gains would be observed in bimodally rather than unimodally trained amusics from pretest to posttest, which resembles the performance profile in typical listeners (Erickson & Thiessen, 2015;Ong et al, 2015aOng et al, , 2016Ong et al, , 2017aThiessen, 2017).…”
Section: The Present Studymentioning
confidence: 94%
See 2 more Smart Citations
“…Therefore, /y/ was used to substitute for it, and there is a glide between alveopalatal affricates and the nucleus /a/. Despite the fact that Mandarin is a tone language ( Zhu et al, 2022 ), tones were not controlled when selecting the target words due to the issue of familiarity and picturability. The purpose was to the greatest extent to make sure that children in this age range could readily recognize these pictures without heavy cognitive load in case they felt frustrated and withdrew during recording.…”
Section: Methodsmentioning
confidence: 99%